Reklamasi Pantai Kota Manado dalam Perspektif Hukum Lingkungan dan Tata Ruang: Kritik terhadap Ketiadaan Partisipasi Publik - Gregorius Warow; Muhammad Zaki Mubarrak (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Coastal reclamation as an effort to develop coastal areas often raises legal, environmental, and social issues, especially related to public participation. This study analyzes reclamation projects in Manado Beach with an environmental and spatial planning law approach. It was found that this reclamation has the potential to violate the principles of sustainability and public participation as stipulated in various regulations, including the PPLH Law and the Manado City RTRW. Although the 2023 Regional Regulation emphasizes environmental mitigation and protection, its implementation has not yet reflected maximum community involvement. This study emphasizes the importance of public involvement as a control instrument for wide-ranging reclamation policies.